Hausaufgaben im Unterricht Ethnographie eines schulischen Entgrenzungsphänomens - Fuhrmann, Laura (Verlag Julius Klinkhardt, 2022)
Homework is set in two locations: On the one hand, homework is a task initiated in class, but on the other hand, it has to be done outside of class. Starting from that, the ethnographic study investigates how this division is reflected in the classroom and how it is negotiated by teachers and students. Homework becomes an occasion for the dissolution of boundaries in the classroom. By requesting to work outside of the classroom, the boundaries between the school and the private field are dissolved. Using a practice-theoretical approach, the study reconstructs how the access of school to the private field takes shape via homework and how students also succeed in counteracting these delimitations. On the basis of the reconstructions, information can be gained about the central importance of homework for school and teaching: The outsourcing of tasks not only relieves the lesson, but at the same time delegates the responsibility for learning to areas outside of school. By proceeding this delegation along classist attributions about the educational orientation of students' parents, homework proves to be a mechanism of (re)production of inequality.